Application of easy rotary aeration composter (Ezrac) for composting vegetables waste - Awang, Zarizi; Teh, Er Jing; Tajul Baharuddin, Muhamad Faizal; Hashim, Nor Haslina (Penerbit UTHM, 2020)
Malaysia experiences a great development and diversifies its economy in manufacturing, services, and tourism, particularly after 1981. As many other developing countries, Malaysia faces conflict between economic growth and conservation of environment. However, it has recognised the concept of sustainable development and has embedded this concept in its policies, vision, mission, and plans.